2007
DOI: 10.1016/j.neuroscience.2007.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of central trigeminovascular neurons: Blockade by intravenous naproxen infusion

Abstract: We have previously observed that migraine attacks impervious to triptan therapy were readily terminated by subsequent intravenous administration of the non-steroidal anti-inflammatory drug (NSAID) ketorolac. Since such attacks were associated with periorbital allodynia -a symptom of central sensitization -we examined whether infusion of the NSAID naproxen can block sensitization of central trigeminovascular neurons in the medullary dorsal horn, using in vivo single-unit recording in the rat. Topical exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 40 publications
5
66
0
2
Order By: Relevance
“…Highly soluble aspirin 1000 mg is effective in migraine (8) but its mode of action in migraine is uncertain. Animal studies indicate that NSAIDs, including aspirin, may inhibit central trigeminal neurons in nucleus caudalis (9,10). This mechanism of action should work for all kinds of pain in the head, but aspirin was without any effect in the present vascular headache model.…”
Section: Choice Of Validation Drugsmentioning
confidence: 71%
“…Highly soluble aspirin 1000 mg is effective in migraine (8) but its mode of action in migraine is uncertain. Animal studies indicate that NSAIDs, including aspirin, may inhibit central trigeminal neurons in nucleus caudalis (9,10). This mechanism of action should work for all kinds of pain in the head, but aspirin was without any effect in the present vascular headache model.…”
Section: Choice Of Validation Drugsmentioning
confidence: 71%
“…It has been suggested that individuals with central sensitization respond poorly to tritpans but not to NSAIDs. 33,34 Perhaps drugs that directly address migraine-related inflammation may prevent or reverse central sensitization and the risk of TM. In individuals with high frequency of attacks, central sensitization is frequently present even between the attacks 17 and, accordingly, the NSAIDs would not be protective.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown that some antimigraine drugs of different pharmacological classes, such as triptans (Goadsby and Knight, 1997), non-steroidal anti-inflammatory drugs (Jakubowski et al, 2005(Jakubowski et al, , 2007Sokolov et al, 2010), and calcitonin gene-related peptide receptor antagonists (Storer et al, 2004a) produce considerable inhibition of spike activity of the spinal trigeminal neurons, indicating a key aspect of their pharmacodynamics. In the present study, the use of non-pharmacological but clinically proven effective physiotherapeutic technique resulted in analogous changes in trigeminal neuronal activity.…”
Section: Discussionmentioning
confidence: 99%